Peningkatan Kemampuan Representasi Matematis Siswa Menggunakan GeoGebra - Ari Septian; Erwan Setiawan; Yesi Noersapitri (LPPM Universitas Advent Indonesia, 2023)
Mathematical representation ability is one of the important abilities of learning mathematics. This study aims to determine whether the increase in the mathematical representation ability of students who receive learning using GeoGebra is better than students who receive learning using ordinary learning. The research method used is a quasi-experimental method with the design form The Nonequivalent Pretest-Posttest Control Group Design. The population of this research is the students of class X SMK PGRI 1 Tourism Cianjur. Involving a sample of 31 students from two classes selected through purposive sampling technique. Class X Catering and Dressing as an experimental class and class X Banking as a control class. The instrument used is a test instrument in the form of pretest and posttest to measure the ability of mathematical representation and non-test in the form of an attitude scale questionnaire. Analysis of quantitative data in this study using SPSS 24. The results of the analysis show that the improvement of mathematical representation skills using GeoGebra is better than mathematical representation skills using ordinary learning. And students like the use of GeoGebra in learning mathematics.